2019
DOI: 10.3389/fgene.2019.01219
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the RFC1 Repeat Expansion in a Canadian and a Brazilian Ataxia Cohort: Identification of Novel Conformations

Abstract: A biallelic pentanucleotide expansion in the RFC1 gene has been reported to be a common cause of late-onset ataxia. In the general population, four different repeat conformations are observed: wild type sequence AAAAG (11 repeats) and longer expansions of either AAAAG, AAAGG or AAGGG sequences. However only the biallelic AAGGG expansions were reported to cause late-onset ataxia. In this study, we aimed to assess the prevalence and nature of RFC1 repeat expansions in three cohorts of adult-onset ataxia cases: B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 11 publications
6
64
1
3
Order By: Relevance
“…In addition, this locus is highly polymorphic, because other PNRs have been identified: (AAAAG) exp , (AAAGG) exp , (AAGAG) exp , and (AGAGG) exp . 4,6,7 In the present study, we screened the PNRs of RFC1 in Chinese SAOA, MSA, and unaffected cohorts. We identified a biallelic AAGGG expansion in RFC1 in 1 SAOA patient and 3 MSA patients, ranging from 100 to 160 repeats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, this locus is highly polymorphic, because other PNRs have been identified: (AAAAG) exp , (AAAGG) exp , (AAGAG) exp , and (AGAGG) exp . 4,6,7 In the present study, we screened the PNRs of RFC1 in Chinese SAOA, MSA, and unaffected cohorts. We identified a biallelic AAGGG expansion in RFC1 in 1 SAOA patient and 3 MSA patients, ranging from 100 to 160 repeats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identified the heterozygous (AAGGG) exp /(AAAGG) exp genotype in an MSA patient, which was identified in 2 LOCA patients (including 1 CANVAS patient) and 2 healthy subjects. 4,6,7 Thus, whether the heterozygous (AAGGG) exp /(AAAGG) exp genotype is pathogenic remains unclear. We observed that the percentage of positive cases was only 0.96% in Chinese SAOA cohorts, much lower than the percentage in European LOCA cohorts (22%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations